English language teaching research in South Korea: A review of recent studies (2009–2014). (7th December 2015) - Moodie, Ian; Nam, Hyun-Jeong
Abstract : This article reviews recent studies on English language teaching (ELT) in South Korea, where a great deal of research has been produced in recent years in local journals. In this article we review 95 studies from a pool of some 1, 200 published between 2009 and 2014 on English language teaching and learning, focusing on research within the public school context. Using themes from the national curriculum as an organizing principle, the review covers selected studies in the following areas: (1) second language teacher education, (2) communicative language teaching, (3) language use and interaction in classrooms, (4) co-teaching with native-speaking English teachers, (5) curriculum and materials analysis, (6) treatments of teaching methods, and (7) assessment, testing and washback. We include commentary on the research undertaken in each area and conclude by discussing the limitations of the review and summarizing ideas for future research directions, perhaps the most important of which is questioning whether or not there is enough research of reasonable quality being produced to sustain roughly 60 journals publishing articles on English education in South Korea.